TINDAK TUTUR DAN PERISTIWA TUTUR - Purba, Andiopenta (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article gives critical analysis of two important aspect of oral communication, speech act and speech event. Speech act is an individual symptom which has psychological behavior determined by language competence of speaker in specific circumstances. Conversely, speech event related to social symptom which involves participants in one main speech, time, place, and certain context. Keywords: speech act, speech event